Understanding Dengue Virus Capsid Protein Interaction with Key Biological Targets - Faustino, André F. (2016)
Dengue virus (DENV) causes over 500,000 hospitalizations and 20,000 deaths worldwide every year. Dengue epidemics now reach temperate regions due to globalization of trade and travel and climate changes. Currently, there are no successful therapeutic or preventive approaches. We previously developed a peptide drug lead, pep14-23, that inhibits the biologically relevant interaction of DENV capsid (C) protein with lipid droplets (LDs). Surprisingly, pep14-23 also inhibits DENV C interaction with very low-density lipoproteins (VLDL). We thus investigated the similarity between the proposed DENV C molecular targets in LDs and VLDL, respectively, the proteins perilipin 3 (PLIN3) and apolipoprotein E (APOE). APOE N-terminal and PLIN3 C-terminal regions are remarkably similar, namely APOE α-helix 4 (APOEα4) and PLIN3 α-helix 5 (PLIN3α5) sequences, which are also highly superimposable structurally. Interestingly, APOE α-helical N-terminal sequence and structure superimposes with DENV C α-helices α1 and α2. Moreover, the DENV C hydrophobic cleft can accommodate the structurally analogous APOEα4 and PLIN3α5 helical regions. Mirroring DENV C-LDs interaction (previously shown experimentally to require PLIN3), we experimentally demonstrated that DENV C-VLDL interaction requires APOE. Thus, the results fit well with previous data and suggest future drug development strategies targeting the above mentioned α-helical structures.